In the Arena of the Picture. Performing as a Threshold of Modernism According to Harold Rosenberg and Clement Greenberg, including Allan Kaprow - Sessa, Marcello (Eikón / Imago, 2022)
In the present essay, I aim to reinterpret the notion of performing in respect of modernist ontologies of art, with a particular focus on American art criticism in the mid-twentieth century. Firstly, I will address to art critics such as Clement Greenberg but especially Harold Rosenberg, as forerunners in acknowledging theoretical importance to the very concept of performing, and in pointing out its leading role in the development of contemporary art. I will analyse the implications of the work of art as a performance in Rosenberg’s formulation of “action painting” as the arena of artistic creation, and in Greenberg’s conception of modernist painting as autonomous and self-determined. I will proceed in verifying the impact of this “performative turn” from the painting to the evironment and the pure event, taking for example Allan Kaprow’s theory of happening and nonart. I will compare it with Rosenberg and Greenberg’s achievements. As a result, I will suggest that performing could be seen, at the same time, as a threshold of modernism and also as a shift towards postmodernism.